Continuing medical education for general practitioners in Indonesia: Moving toward accountability - Yusring Sanusi Baso; Amir Syafruddin; Abraham Andi Padlan; Muhammad Akbar (Elsevier, 2021)
Objective: The purpose of this study is to determine the effect of an online continuing medical education model on the learning outcomes of general practitioners (GPs) in Indonesia. Methods: The method used in this research is a pre-experimental pre-test, post-test group design. 1449 GPs originating from the major islands of Indonesia participated in this study. One hundred fifty questions from 10 disease systems were prepared for the pre-test and post-test with a total score of 100. The results of the pre-test and post-test were tested with paired sample t-test and Independent t-test. Results: The paired sample t-test revealed significant differences in the learning outcomes of GPs before and following the online module's continuing medical education approach. What is remarkable is the disparity in average post-test results between GPs in West and East Indonesia. The independent t-test revealed that the average post-test score of general practitioners in western Indonesia was higher than that of general practitioners in eastern Indonesia. Conclusion: The findings of this study suggest that continuing medical education in the form of online learning can help general practitioners enhance their knowledge and abilities in disease management. This paradigm of online continuing medical education could be adapted for other professions.